КОРЕЯ МЕН ҚЫТАЙ АРАСЫНДАҒЫ САЯСИ ЖӘНЕ ДИПЛОМАТИЯЛЫҚ ҚАТЫНАСТЫҢ ТАРИХИ АСПЕКТІЛЕРІ. (Journal of Oriental Studies, 2016)
Корею и Китай связывают многолетние тесныеотношения. Давним корейским государством приходи-лось держать мир с гигантской древней империи, кото-рая оказывала очень сильное влияния на корейскийполуостров. В данной статье говорится и теченииполитическо-дипломатических отношении Кореи иКитая с конца VII века – начала XX века.Korea and China are linked long-term close relationship.Longtime Korean government had to keep the peacewith a giant of the ancient empire, which has a verystrong influence on the Koreanpeninsula. The article says,and within the political and diplomatic relations betweenKorea and China since the end of VII century - beginningof XX century.